The Land of Storms and the region where the country’s heart beats: changing images of peripherality in Hungary - Balogh, Péter (Hungarian Geographical Bulletin, 2015)
Processes of peripheralisation have over the past years been studied from structuralist and discursive angles alike. There is at the same time a growing awareness that the two need to be studied together. This paper makes an attempt by showing how socio-material and discursive processes can co-constitute centre-periphery relations, on the example of Hungarian regions. Particular focus is given to Békés County as well as to Central Hungary. The empirical sources consist of sociographic books and popular scientific articles written mostly by geographers. The former show that images of peripheral areas have signifi cantly altered over time. While the "Land of Storms" - an epithet associated with Békés County - for instance has typically stood for toughness and combat-readiness up until the 1950s, it has been connected more with passivity and tardiness since the 1980s. Despite the changing nature of these images they have curiously always been attributed to the region´s peripherality, even though a rising spirit for instance has not been a typical feature of peripheries in Hungary. The analysis of popular scientific articles reveals that they are usually written from the centre´s perspective, targeting the centre´s audience. Further, certain places are peripheralised by being depicted as forgott en or remote; the natural endowments of rural and sparsely populated areas are not rarely exotified and romanticised. Such descriptions may make so-called peripheries more interesting for readers (in the centres), yet they also maintain old images of such areas that can considerably affect their development potentials.